Translation initiation consistency between in vivo and in vitro bacterial protein expression systems - Li, Jiaojiao; Li, Peixian; Liu, Qian; Li, Jinjin; Qi, Hao (Frontiers in Bioengineering and Biotechnology, 2023)
Strict on-demand control of protein synthesis is a crucial aspect of synthetic biology. The 5'-terminal untranslated region (5′-UTR) is an essential bacterial genetic element that can be designed for the regulation of translation initiation. However, there is insufficient systematical data on the consistency of 5′-UTR function among various bacterial cells and in vitro protein synthesis systems, which is crucial for the standardization and modularization of genetic elements in synthetic biology. Here, more than 400 expression cassettes comprising the GFP gene under the regulation of various 5′-UTRs were systematically characterized to evaluate the protein translation consistency in the two popular E. coli strains of JM109 and BL21, as well as an in vitro protein expression system based on cell lysate. In contrast to the very strong correlation between the two cellular systems, the consistency between in vivo and in vitro protein translation was lost, whereby both in vivo and in vitro translation evidently deviated from the estimation of the standard statistical thermodynamic model. Finally, we found that the absence of nucleotide C and complex secondary structure in the 5′-UTR significantly improve the efficiency of protein translation, both in vitro and in vivo.